The stock market as a leading indicator of economic activity: time-series evidence from South Africa - Sayed, Ayesha (My University, 2016)
Several studies have assessed the forward-looking characteristic of share prices and confirmed their resultant capability as leading indicators of economic activity, especially in advanced economies. Contention however exists when evaluating the role of stock markets as leading indicators for less developed countries. This study examines the validity of the stock market as a leading indicator of economic activity in South Africa using quarterly time-series data for the period January 1992 to June 2014. Causality and cointegration between the JSE All Share Index against Real GDP and Real Industrial Production is evaluated by employing Granger-causality tests and the Johansen cointegration procedure. The empirical investigation indicates that unidirectional causality exists between the nominal and real stock indices and economic activity in South Africa, and confirms a long-run relationship between the JSE and GDP and Industrial Production. Therefore, similar to the study by Auret and Golding (2012), in a South African context, the stock market is in fact a leading indicator of economic activity.
A 50% research report to be submitted in partial fulfilment for the degree of: MASTER OF COMMERCE (FINANCE) UNIVERSITY OF THE WITWATERSRAND
Keywords: Stocks--Prices--South Africa; Johannesburg Stock Exchange; Time-series analysis; Stock price forecasting--South Africa